Archi-écritures de genre et politiques de différance : immondices verbales et littéracies d’intervention dans le quotidien des établissements scolaires - Rodrigo Borba; Adriana Carvalho Lopes (Glad!)
In 2015, rumours about the fact that Colégio Pedro II had established the use of the letter X as a strategy to erase (grammatical and social) gender triggered linguistic guerilla wars (Cameron, 2012) among experts and language users. In the same year, during the LGBT week at UFRRJ, signs with similar linguistic disruptions the organizers of the event had put up on the doors of the restrooms around campus provoked revolt among students, faculty members and other employees. In this scenario, in dialogue with Derrida, we investigate discourses about the erasure of (grammatical) gender in the mainstream media and in teaching institutions. Against this backdrop, we aim to analyze the relationship between language, society, citizenship, and literacies. Grounded on the analytical assumption that language (and, above all, what we do with it and speak about it) cannot not be sidelined if we want to understand historical moments of political and social turbulence, we argue that these semiotic interventions mess linguistic conventions and school’s everyday life and, thus, challenge power relations. We conclude that these linguistic interventions may open up possibilities to “make a difference”, i.e. to repeat reality in different ways, to (re)imagine futures and to (re)design territories in ways that liberate them from fixed, purist and well-circumscribed concepts and practices.